Respuesta :

Space

Answer:

[tex]f(x) = \frac{x^4}{12} - sin(x) + 3x + 4[/tex]

General Formulas and Concepts:

Calculus

  • Antiderivatives
  • Integration Constant C
  • [Int Rule] Reverse Power Rule: [tex]\int {x^n} \, dx = \frac{x^{n+1}}{n+1} + C[/tex]
  • Integration Property 1: [tex]\int {cf(x)} \, dx = c\int {f(x)} \, dx[/tex]
  • Integration Property 2: [tex]\int {f(x)+g(x)} \, dx = \int {f(x)} \, dx + \int {g(x)} \, dx[/tex]

Step-by-step explanation:

Step 1: Define

f"(x) = x² + sin(x)

Condition f'(0) = 2

Condition f(0) = 4

Step 2: Integrate Pt. 1

  1. Set up:                                                                                                   [tex]f'(x) = \int {f"(x)} \, dx[/tex]
  2. Substitute:                                                                                            [tex]f'(x) = \int [{x^2 + sin(x)}] \, dx[/tex]
  3. Rewrite [Int Property 2]:                                                                          [tex]f'(x) = \int {x^2} \, dx + \int {sin(x)} \, dx[/tex]
  4. Integrate [Reverse Power Rule/Trig]:                                                    [tex]f'(x) = \frac{x^3}{3} - cos(x) + C[/tex]

Step 3: Find f'(x)

Use the given condition to find the differential equation.

  1. Substitute:                    [tex]f'(0) = \frac{0^3}{3} - cos(0) + C[/tex]
  2. Substitute:                    [tex]2 = \frac{0^3}{3} - cos(0) + C[/tex]
  3. Evaluate:                      [tex]2 = 0 - 1 + C[/tex]
  4. Solve:                           [tex]3 = C[/tex]
  5. Define:                         [tex]f'(x) = \frac{x^3}{3} - cos(x) + 3[/tex]

Step 4: Integrate Pt. 2

  1. Set up:                                                                                                   [tex]f(x) = \int {f'(x)} \, dx[/tex]
  2. Substitute:                                                                                              [tex]f(x) = \int [{\frac{x^3}{3} - cos(x) + 3}] \, dx[/tex]
  3. Rewrite [Int Property 2]:                                                                                [tex]f(x) = \int {\frac{x^3}{3} } \, dx + \int {-cos(x)} \, dx + \int {3} \, dx[/tex]
  4. Rewrite [Int Property 1]:                                                                            [tex]f(x) = \frac{1}{3} \int {x^3} \, dx - \int {cos(x)} \, dx + \int {3} \, dx[/tex]
  5. Integrate {Reverse Power Rule/Trig]:                                                      [tex]f(x) = \frac{1}{3}(\frac{x^4}{4} ) - sin(x) + 3x + C[/tex]
  6. Simplify:                                                                                                    [tex]f(x) = \frac{x^4}{12} - sin(x) + 3x + C[/tex]

Step 5: Find f(x)

Use the given condition to find the equation.

  1. Substitute:                    [tex]f(0) = \frac{0^4}{12} - sin(0) + 3(0) + C[/tex]
  2. Substitute:                    [tex]4 = \frac{0^4}{12} - sin(0) + 3(0) + C[/tex]
  3. Evaluate:                       [tex]4 = 0 - 0 + 0+ C[/tex]
  4. Solve:                            [tex]4 = C[/tex]
  5. Define:                          [tex]f(x) = \frac{x^4}{12} - sin(x) + 3x + 4[/tex]
ACCESS MORE